Impact of Non-Performing Loans on Bank Profitability and Lending Behavior in Nepalese Commercial Banks - Pradhan, Priya; Jha, Puja; Sah, Puja; Magar, Ram Bahadur (Nepalese Journal of Economics, 2024)
This study examines the impact of non-performing loans on bank profitability and lending behavior in Nepalese commercial banks. Return on assets and loan and advances are selected as the dependent variables. Similarly, capital adequacy ratio, credit to deposit ratio, non-performing loan, equity to total assets, bank size, gross domestic product growth and inflation rate are selected as the independent variables. This study is based on secondary data of 16 commercial banks with 112 observations for the study period from 2016/17 to 2022/23. The data were collected from Banking and Financial statistics published by Nepal Rastra Bank, reports published by the Ministry of Finance, and annual reports of respective banks. The correlation coefficients and regression models are estimated to test the impact of non performing loans on bank profitability and lending behavior of Nepalese commercial banks. The study showed that capital adequacy ratio has a positive impact on return on assets. It means that increase in capital adequacy ratio leads to increase in return on assets. Likewise, non-performing loan has a negative impact on return on assets. It means that increase in non performing loan leads to decrease in return on assets. On the other hand, the result showed that credit to deposit ratio has a positive impact on loans and advances. It shows that higher the credit to deposit ratio, higher would be the loans and advances. Further, this study showed that equity to total assets has a positive impact on return on assets. It means that increase in equity to total assets leads to increase in return on assets. Moreover, inflation rate also has a negative impact on return on assets which means that increase in inflation rate leads to decrease in return on assets. Furthermore, bank size has a positive impact on loans and advances. It indicates that increase in bank size leads to increase in loans and advances. Similarly, GDP growth rate has a positive impact on loans and advances. It means that increase in GDP growth rate leads to increase in loans and advances.